Influence of Knowledge, Attitude, and Behavior on Hospital Workers' Vitamin D - Febriarto*, Dimas; Makarim, Fadhli Rizal; Rizaldy, Rheza (Universitas Syiah Kuala, 2023)
This study aims to determine the role of knowledge, attitudes, and behaviors in relation to vitamin D levels among hospital workers who have limited sunlight exposure and those who are exposed to sunlight. This cross-sectional study were conducted on 54 participants randomly selected from hospital outdoor worker, clinic worker, and operating room worker. The participants completed a validated Vitamin D knowledge, attitude, and behaviour questionnaire. Blood samples were collected to measure 25(OH)D using ELISA method. Mann-whitney test was used to assess Vitamin D level between groups, while influence of knowledge, attitude, and behaviour on vitamin D levels were assessed using Chi-square test.